The effects of CaCO3 on the properties of PCL wood-plastic composites. Issue 2 (February 2019) - Zhang, Qiong; Li, Yi; Wen, Jun; Yuan, Song; Zhu, Zhifeng
Abstract: The effects of CaCO3 on the properties of PCL wood-plastic composites were studied in this paper. The strength and the melt flow rate of the composites increased first and then decreased with the content of CaCO3, and up to maximum while the content of CaCO3 is 30%. Gaps and holes could be seen from the SEM figure in the composites when the content of CaCO3 is more than 30%. Above all, the best content of CaCO3 in the composites is 30%.